Effect of filler loading, geometry, dispersion and temperature on thermal conductivity of polymer nanocomposites. (February 2017) - Tessema, Addis; Zhao, Dan; Moll, Joseph; Xu, Shansan; Yang, Ronggui; Li, Chen; Kumar, Sanat K.; Kidane, Addis
Abstract: Using a unidirectional heat transfer apparatus, the roles of nanoparticle geometry, loading, dispersion and temperature on the thermal conductivity of polymer nanocomposites are investigated. The polymer nanocomposites (PNC) consist of epoxy matrices filled with silica nanopowder and carbon nanotubes, respectively, as well as poly (2-vinylpyridine) (P2VP) matrices loaded with silica nanoparticles. First, it is shown that thermal conductivity generally increases with nanofiller loading. These results are also reasonably described by the three phase Lewis-Nielsen or Halpin-Tsai analytical models. More importantly, it has been also demonstrated that the thermal conductivity of the polymer nanocomposites greatly depends on the dispersion state of the nanofillers. Furthermore, the effect of temperature on the thermal behavior of PNCs is briefly discussed. These results emphasize the important role of nanoparticles content and dispersion state on the thermal characteristics of polymer nanocomposites, which can be used to design composite materials with tunable thermal behavior.